Isolated and Bidirectional two-stage DC/AC converter with grid-forming virtual inertia and high ripple on the DC bus for Single-Phase Grid applications - Zarate A. (2021)
ACKNOWLEDGMENT This work was financed by CONCYTEC-FONDECYT within the call for projects E041-01 [Contract Number 031-2019]